Implementation of Lossless Voice Data Communication using Network Streams on Embedded System - Prasetio, Barlian Henryranu; Syauqy, Dahnial (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
Smart home refers to the use of computers and information technology to control home appliances. The smart home system occupies sensors to acquire data for monitoring. One of the most important factors in designing a smart home system was the communication between devices that will be used. It requires high throughput and low latency communication so that monitoring can be done in real time and lossless. The communication network was designed to optimize the stream monitoring for smart home by reviewing the system throughput and latency. Lab-VIEW programming on My-RIO embedded systems was used to acquire accelerometer and voice data readings and send them to personal computer wirelessly. The network communication was designed by implementing network stream protocols between two applications which were planted in the personal computer and My-RIO system. The test results indicate that the network stream protocol did not require normalization of sensor data types while transmitting and receiving. The throughput values were affected by increasing buffer size but on certain conditions saturated throughput were experienced. The value of the latency is always stable with an average value of 13 ms even though the size of the buffer is enlarged.